Pectus arcuatum: Description of a hybrid surgical technique - Isabel González-Barba; Ana Laín; Laura García; Carlos Giné; Manuel López (Elsevier, 2023)
Objetives: Pectus Arcuatum (PA) is a very rare anterior chest wall deformity resulting from premature obliteration of the sternomanubrial junction. Unlike other chest wall deformities, surgical correction continues to be the only treatment option. We report our initial experience using the hybrid technique and evaluate the results. Methods: We reviewed all the cases of PA that underwent a hybrid procedure between January 2020 and June 2022.We combined the Nuss procedure and the modified-Ravitch procedure. All patients underwent either percutaneous or thoracoscopic cryoanalgesia to improve postoperative pain management. The Nuss procedure was performed first. A single bar was inserted under thoracoscopic vision.Sternochondroplasty was performed through a 3-4-centimeter-long mid-sternal skin incision. After dissecting the sternal insertions of both pectoralis major muscles, bilateral subperichondrial chondrectomies were carried out and a wedge-shaped transverse sternal osteotomy was performed using an oscillating saw, preserving the posterior lamina. Sternal realignment was achieved by securing opposite sides of the osteotomy with two vertical titanium plates. Results: Three patients with PA were subjected to the hybrid procedure between January 2019 and June 2022. The mean age was 15 years (14-16). No intraoperative complications were encountered. The mean operative time was 200 minutes. Postoperative radiography showed optimal sternal realignment and stabilization. Excellent esthetic results were obtained with high patient satisfaction in all cases. The overall hospital stay ranged from four to five days in all cases with optimal pain control. The mean follow-up was 26.6 months (6-38), recurrence was not noted after bar removal. Conclusions: The simultaneous correction of the sternal depression, with the insertion of a single pectus bar, during the hybrid procedure enables surgeons to perform a less invasive sternochondroplasty and a single sternal wedge-osteotomy through a smaller and more esthetic mid-sternal skin incision, whilst maintaining chest-wall stability. The hybrid technique is a novel procedure that has been carried out successfully in the 3 cases reported in our study, with excellent esthetic results. To our knowledge cryoanalgesia has not been previously employed to better the postoperative pain management of patients undergoing surgical correction for PA.